The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1982
DOI: 10.1126/science.6760398
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Damage in Escherichia coli K12 AB2480 by Broad-spectrum Near-Ultraviolet Radiation

Abstract: Irradiation with either broad-spectrum near-ultraviolet [fluorescent BLB (black light blue)] or monochromatic wavelengths in the near-ultraviolet range (320 to 400 nanometers) can cause specific damage to DNA as shown in experiments with Escherichia coli K12 AB2480 at the stationary phase of growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Some contributions use mutagenicity and genetic approaches to identify near-UV (NUV, 320–400 nm) radiation effects on bacteria cells. Webb and Brown demonstrated that irradiation with either broad-spectrum NUV or monochromatic wavelengths in the NUV can cause specific damages to DNA in E. coli K12 AB248040. Eisenstark studied the DNA mutations due to NUV in E. coli .…”
Section: Discussionmentioning
confidence: 99%
“…Some contributions use mutagenicity and genetic approaches to identify near-UV (NUV, 320–400 nm) radiation effects on bacteria cells. Webb and Brown demonstrated that irradiation with either broad-spectrum NUV or monochromatic wavelengths in the NUV can cause specific damages to DNA in E. coli K12 AB248040. Eisenstark studied the DNA mutations due to NUV in E. coli .…”
Section: Discussionmentioning
confidence: 99%
“…Other lesions such as the (6–4) pyrimidine–pyrimidone photoproducts are even more proficient in stopping DNA synthesis (57). The distribution of photoproducts accumulating in cells upon UV irradiation is different for different UV regions and also varies between vegetative cells and spores (3,24,33,58–70). In vegetative cells dimers predominate in bacterial DNA after exposure to UVC.…”
Section: Uv Damage and Repairmentioning
confidence: 99%